2002
DOI: 10.1002/eqe.224
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the inelastic response of base isolated buildings

Abstract: SUMMARYThis article presents a numeric comparative study of the inelastic structural response of base isolated buildings. The comparative study includes the following isolation systems: laminated rubber bearings, New Zealand one, pure friction and the frictional pendulum ones. The study is based on obtaining nonlinear response spectra for various design parameters using six earthquake records. Usually the base isolation of a new building seeks to maintain the structure in the linear elastic range. The response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 6 publications
0
33
0
Order By: Relevance
“…For additional information about friction pendulum systems the reader is referred to the relevant literature (e.g. [33], [34], [35], [36], [37] and [38]). More detailed examination of this topic would lead beyond the scope of this paper, which should focus more on the methodical extension of the new MOR strategy as well as the application on a complex realistic system.…”
Section: Dynamic Model Of the Frictional Pendulum Elementmentioning
confidence: 99%
“…For additional information about friction pendulum systems the reader is referred to the relevant literature (e.g. [33], [34], [35], [36], [37] and [38]). More detailed examination of this topic would lead beyond the scope of this paper, which should focus more on the methodical extension of the new MOR strategy as well as the application on a complex realistic system.…”
Section: Dynamic Model Of the Frictional Pendulum Elementmentioning
confidence: 99%
“…Constantinou and Quarshie [4], Ordonez et al [5], Kikuchi et al [6], Thiravechyan et al [7] and Cardone et al [8] investigated the response of inelastic seismically isolated structures and agreed that allowing base-isolated superstructures to yield requires careful consideration because of possible occurrence of large ductility demands. Vassiliou et al [9][10][11] concluded that designing typical seismically isolated structures to behave elastically, as prescribed by current seismic design codes, is not overly conservative but a necessity that emerges from the fundamental dynamics of such structures.…”
Section: Introductionmentioning
confidence: 99%
“…The uncertain nature of these events renders their effective mitigation a non-trivial task. In addressing this issue, isolation systems have been developed and applied for protecting structural systems, by permitting relative motion with respect to the base (Mao and Li, 2005;Ordonez et al, 2003;Kelly, 1990). Nonetheless, the design of these systems is not straightforward, and a number of bottlenecks have been identified and reported (Providakis, 2009) including reduced resistance to vertical deformation, and large horizontal displacements, which call for additional damping elements, with increased costs and no guarantee of adequacy.…”
Section: Introductionmentioning
confidence: 99%